2005
DOI: 10.1242/dev.01958
|View full text |Cite
|
Sign up to set email alerts
|

Fgf8 drives myogenic progression of a novel lateral fast muscle fibre population in zebrafish

Abstract: Fibroblast growth factors (Fgfs) have long been implicated in regulating vertebrate skeletal muscle differentiation, but their precise role(s) in vivo remain unclear. Here, we show that Fgf8 signalling in the somite is required for myod expression and terminal differentiation of a subset of fast muscle cells in the zebrafish lateral somite. In the absence of Fgf8, lateral somite cells transiently express myf5 but fail to make muscle and remain in a dermomyotome-like state characterised by pax3 and meox express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
162
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(171 citation statements)
references
References 76 publications
(71 reference statements)
8
162
1
Order By: Relevance
“…The expression of myl1 was decreased in ace mutants (Fig. 5), which correlates to the decreased expression of myod in the lateral part of the ace myotome, as previously described (Groves et al, 2005). The myl1 expression domain expanded into the adaxial cells in ubo mutants, which indicates that myl1 is transcriptionally repressed by Prdm1 in adaxial cells in wild type embryos (Fig.…”
Section: Regulation Of Myl1 Expressionsupporting
confidence: 85%
See 3 more Smart Citations
“…The expression of myl1 was decreased in ace mutants (Fig. 5), which correlates to the decreased expression of myod in the lateral part of the ace myotome, as previously described (Groves et al, 2005). The myl1 expression domain expanded into the adaxial cells in ubo mutants, which indicates that myl1 is transcriptionally repressed by Prdm1 in adaxial cells in wild type embryos (Fig.…”
Section: Regulation Of Myl1 Expressionsupporting
confidence: 85%
“…Already at early gastrula stages, the lineage traces have concluded that mesodermal cells are predestined to either the slow or the fast pathway depending on their respective localization in the embryo (reviewed in Ochi and Westerfield, 2007). The myogenic fate, however, is determined during early somitogenesis by the inductive signals of FGF and hedgehog signalling pathways, where FGF signalling, at least in the lateral part of the presomitic mesoderm, results in fast muscle development and hedgehog signalling from the notochord leads to the specification of adaxial cells and slow fate Coutelle et al, 2001;Blagden et al, 1997;Lewis et al, 1999, Groves et al, 2005.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel with this process, cells in the anterior somite border generate a Pax3/7-expressing DM external cell layer Groves et al, 2005;Hammond et al, 2007;Hollway et al, 2007;. Cells of the DM appear to contribute to later muscle growth .…”
Section: Introductionmentioning
confidence: 97%